2019
DOI: 10.3389/fmicb.2019.02854
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activity of Temporin-GHc and Temporin-GHd Against Cariogenic Bacteria, Streptococcus mutans

Abstract: Temporin-GHc (GHc) and temporin-GHd (GHd) produced by the frog Hylarana guentheri had shown broad-spectrum antibacterial activities against bacteria and fungi. In this study, we investigated whether they exert antibacterial and antibiofilm activities against cariogenic bacteria, Streptococcus mutans. GHc and GHd adopt the random coil conformation in aqueous solution and convert to α-helix in membrane mimetic environments by using circular dichroism spectroscope. They are positively charged by histidine, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
20
0
2
Order By: Relevance
“…Further investigation through affecting the gene expression of biofilm regulatory genes, including gtf genes and ftf were identified. A potent inhibitor of gtf genes is reported to be capable of reducing the amount of Gtfs in S. mutans biofilms, thereby inhibiting EPSs production and biofilm formation 34 . Munro et al 7 reported that inactivation of gtfB, -C or ftf drastically reduced virulence properties of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation through affecting the gene expression of biofilm regulatory genes, including gtf genes and ftf were identified. A potent inhibitor of gtf genes is reported to be capable of reducing the amount of Gtfs in S. mutans biofilms, thereby inhibiting EPSs production and biofilm formation 34 . Munro et al 7 reported that inactivation of gtfB, -C or ftf drastically reduced virulence properties of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, forming oligomers in some microenvironments, such as lipopolysaccharides (LPS) of Gram-negative bacteria, could escalate the difficulty for temporin to traverse the outer membrane, which weakens the antimicrobial activity on Gram-negative bacteria [ 30 , 33 ]. Therefore, structural modifications and engineering have been continuously implemented for temporins to improve the therapeutic index and efficacy [ 20 , 26 , 30 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a slimy barrier and adhesion are clearly observed among bacterial colonies under a high magnification view in Figure 14 b. The extracellular polysaccharide-wrapped bacterial colonies exhibit the typical features of biofilms [ 32 ], certifying a successful construction of an in vitro biofilm model.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a slimy barrier and adhesion are clearly observed among bacterial colonies under a high magnification view in Figure 14b. The extracellular polysaccharide-wrapped bacterial colonies exhibit the typical features of biofilms [32], certifying a It can be seen from Figure 13 that the OD value of samples before the biofilm removal test was higher than 0.24, implying a biofilm with vigorous viability. All five curves after the removal tests have a significantly lower value than that of the control, suggesting an evident reduction in biofilm.…”
Section: Sem Of S Aureus Biofilmmentioning
confidence: 87%